Evaluation of a data communication model for switched fibre channel. - Emerson, S. (IEEE Network : the magazine of global information exchange)
The ANSI standard fibre channel is emerging as the networking protocol of choice for high bandwidth applications. Fibre channel is an enabling technology because of the tremendous advantages in speed and latency it provides over existing networking technologies. Applications that weren't feasible before are now possible, and more applications that demand similar performance will follow. Fibre channel is the high performance alternative to existing networking technologies such as FDDI, Fast Ethernet, and ATM. Fibre channel (FC) provides for two different data communication models: connection (class 1 service) and connectionless (class 2 or 3 service). Although interoperable, some of these implementations may not result in optimal performance. There is some disagreement in the FC community as to which is more appropriate. Both have their advantages and disadvantages, and so it's necessary to look at each application individually. The article addresses some of these issues by simulating these two communication models over different switch architectures